PELAKSANAAN RETRIBUSI PARKIR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI KOTA SURABAYA - Purnamasari, Ima; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the role of parking retribution to the Local Own Source Revenue of Surabaya city, to find out the effectiveness of the revenue of parking retribution, and to find out whether the recording and the journal publishing has in accordance with the contract which is written in the Government Regulations No.71 of 2010. Qualitative approach has been applied in this research by the researcher, by performing observation, documentation, and interview methods. The descriptive data analysis, which has been used by the researcher. The result of the research shows that the revenue of parking retribution of Surabaya city in 2009-2014 is relatively fluctuated. It can be seen from the calculation of contribution and the effectiveness of parking retribution in Surabaya city. The optimalization efforts which have been done by the Tranportation Agency is in accordance with the Local Government Regulations of Surabaya city No.1 of 2009. The financial statement which has been prepared by the local revenue and financial management offices up to 2014 is not in accordance with the Government Regulations No.71 of 2010.Keywords: Parking Retribution, Local Own Source Revenue, Contribution, Effectiveness, Optimalization.